Thermodynamic Transient Simulation of a Combined Heat & Power System. (December 2015) - Borelli, Davide; Devia, Francesco; Schenone, Corrado; Spoladore, Alessandro
Abstract: In this paper a numerical model aimed at studying dynamic behavior of CHP (Combined Heat and Power) plants is presented, paying particular attention to the components in which heat transfers take place. The analysis refers to a system powered by an internal combustion engine for a compression ignition type in cogeneration configuration, equipped with two heat extractors: the first one for coolant / water, the second one for exhaust gas / water. The numerical model has been implemented by using Matlab-Simulink software. After a description of the simplifying assumptions adopted for implementing the simulator, the model is exposed in detail with regards to each single element. Then simulation results are reported for two different operating conditions aiming to assess the effectiveness of the model in analyzing the dynamic behavior of CHP plants.